2021
DOI: 10.1002/rev3.3292
|View full text |Cite
|
Sign up to set email alerts
|

Formative assessment and feedback for learning in higher education: A systematic review

Abstract: Feedback is an integral part of education and there is a substantial body of trials exploring and confirming its effect on learning. This evidence base comes mostly from studies of compulsory school age children; there is very little evidence to support effective feedback practice at higher education, beyond the frameworks and strategies advocated by those claiming expertise in the area. This systematic review aims to address this gap. We review causal evidence from trials of feedback and formative assessment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(62 citation statements)
references
References 56 publications
2
49
0
11
Order By: Relevance
“…So, Lai K.-W., Hong K.-S. in the study of digital technology use patterns and descriptions of learning characteristics of practical differences between generations (20 and 30-40-year-old students) were not found. The results of their study showed that generation is not a determining factor in students' use of digital technology for learning, and generation has no radical impact on the learning characteristics of higher education students [33]. Thus, differences in age are not a barrier to effective communication in the digital environment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…So, Lai K.-W., Hong K.-S. in the study of digital technology use patterns and descriptions of learning characteristics of practical differences between generations (20 and 30-40-year-old students) were not found. The results of their study showed that generation is not a determining factor in students' use of digital technology for learning, and generation has no radical impact on the learning characteristics of higher education students [33]. Thus, differences in age are not a barrier to effective communication in the digital environment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are no easy answers to these questions. The Covid-19 pandemic has disrupted teaching in a variety of institutions, especially in higher education (Morris et al, 2021). Electronic learning (e-learning) became the core method of teaching the curriculum during the pandemic (Holubek, 2020).…”
Section: Higher Education and Covid-19mentioning
confidence: 99%
“…One of the ways digital media and especially RSs systems can be utilized in the classroom is through the involvement of learners in a process of formative assessment and feedback, with their consent and active participation (Hargreaves, 2008;Yoon, 2017;Hussein, 2019). Research by Wiliam (2011) and Morris et al, (2021) illustrated that the fundamental importance of a productive formative assessment through timely feedback and discussion of student responses, helps students' progress and improves their metacognitive function.…”
Section: Higher Education and Covid-19mentioning
confidence: 99%
“…Feedback to learners consists of direct feedback and vicarious feedback [10]. Direct feedback refers to feedback from instructors or employers on learners' performance, whereas vicarious feedback is from more experienced learners on their experience and consequences of actions [10,11]. A pedagogical technique that derives from feedback is feedforward, in which learners "interpret and apply .…”
Section: Online Learning and Learning Feedbackmentioning
confidence: 99%
“…Peer feedback is provided among learners during the learning process. It has the clear goals of improving learner performance [10,11]. Course evaluations are solicited confidentially by education institutions for instructor and course assessment.…”
Section: Introductionmentioning
confidence: 99%